Synthetic biology projects in vitro - Forster, Anthony C.; Church, George M.

(untitled) (Genome Research, 2006)
Advances in the in vitro synthesis and evolution of DNA, RNA, and polypeptides are accelerating the construction of biopolymers, pathways, and organisms with novel functions. Known functions are being integrated and debugged with the aim of synthesizing life-like systems. The goals are knowledge, tools, smart materials, and therapies.